A statistical study of the persistency of rain days during the monsoon season at Poona (MAUSAM, 1954)
A 60-year record of June-September precipitation data for Poona has been user to determine the frequency of rain spells of various lengths. It has been found that the frequencies conform closely to a logarithmic series S ( axr | r ). A method of predicting rain-days based on past rain, making use of the observed frequencies has been illustrated. Also, the use of the constant x of the logarithmic series in persistency forecast is discussed. Finally the skill score of a persistency forecast of a rain-day following a rain period of 1,2…days duration has also been determined. Persistency itself may perhaps be construed as a meteorological factor and it may be possible to improve the accuracy of rain forecasts by applying the persistency theory in addition to the existing synoptic techniques.